DIRECT METHOD VS GRAMMAR TRANSLATION METHOD FOR DIFFERENT AGED UZBEK LEARNERS - Kamola Jonuzokova Elham kyzi; Ilkhomova Rukhshona Ilyos kyzi (Galaxy International Interdisciplinary Research Journal, 2022)
Learning foreign languages is indispensable in these days for everyone, then teachers and their strategies play the big role for students while getting to know language. I am an instructor in the educational language center which is close to my home and I have two elementary groups. I teach them some grammatical rules, instructions and other skills everyday with remarkable methods. Usually I choose methods for my lessons according to my students' needs. For these two my groups, I have chosen two most beneficial methods: direct method and grammar translation method. In this article, I desire to write about these two techniques and how I used them in my work for my students.